THE INFLUENCE OF LEADERSHIP STYLE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN THE VILLAGE OFFICE - Nikma Yucha; Tego Laman Cahyono; Mukti Ali (Ecopreneur.12, 2022)
This study aims to determine the quality and ability to work carefully. An employee needs to have a good level of discipline to be able to maintain and maintain service characteristics. Leadership is a universal phenomenon that can be found in collective life. This type of research used in research is quantitative. The sample in this study was 30 respondents using secondary data. Data analysis techniques in this study are descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. From this evidence, it can be concluded that partially variable variations in leadership style (X1) and work discipline (X2) affect employee performance (Y). Simultaneously. Variable. Leadership style (X1), and. work discipline (X2), affecting employee performance (Y), and work discipline (X2) are the most dominant variables influencing employee performance.